The New Alchemy: Economic liberalism, neoliberalism, and Thomas Pynchon's Against the Day - Carswell, Sean (Textual Practice, 2019)
This article utilises Karl Polanyi's landmark 1944 text The Great Transformation to explicate economic liberalism as it is represented in Thomas Pynchon's Against the Day. Polanyi argues that a fundamental flaw of economic liberalism is its treatment of labour and land as commodities. This commodification leads to economic and ecological disasters. Pynchon demonstrates these disasters throughout his encyclopaedic novel. Further, using Pynchon's metaphor of bilocation – literally being in two places at the same time – this article 'bilocates' the economic liberalism represented in the novel with contemporary neoliberalism, specifically as neoliberalism is characterised by David Harvey and Wendy Brown. Ultimately, this exploration leads to a discussion of freedom within a neoliberal society, particularly as it is envisioned in Pynchon's novel.
English; Literary Studies
Keywords: Against the Day (book); BROWN; Wendy; HARVEY; David; PYNCHON; Thomas; 1937-; economic liberalism; economics; fictitious commodities; globalization; neoliberalism

Summoning Hunger: Polanyi, Piers Plowman, and the Labor Market - Epstein, Robert (Money, Commerce, and Economics in Late Medieval English Literature, 2018)
The “plowing of the half-acre” episode in Langland’s Piers Plowman includes a chilling passage in which Piers summons Hunger to force able but unwilling laborers to work the land. This chapter approaches the episode by way of the economic history of Karl Polanyi, whose critiques of free-market ideology are receiving renewed attention in the context of globalization and the international economic crisis. One of Polanyi’s key points is that the threat of starvation is a prerequisite to the institution of a true labor market—meaning that first the networks of collective support that peasants rely on for survival need to be undermined. The summoning of Hunger shows that Langland is actually more free market in his ideology than are the landowning supporters of the labor statutes.
English (literature);
Keywords: LANGLAND; William; Piers Plowman (book); economic history; globalization; hunger; threat of starvation